The broken circle breakdown [videorecording (DVD)] - Groeningen, Felix van; Heldenbergh, Johan, 1967-; Baetens, Veerle, 1978-; Cattrysse, Nell; Van Rampelberg, Geert; De Caster, Nils; Cleiren, Robbie, 1971-; Huysentruyt, Bert, 1980-; Bijvoet, Jan, 1966-; Heldenbergh, Johan, 1967-; Dobbels, Mieke (2014)
Elise (Veerle Baetens) and Didier (Johan Heldenbergh) fall in love at first sight. She has her own tattoo shop and he plays the banjo in a bluegrass band. They bond over their shared enthusiasm for American music and culture, and dive headfirst into a sweeping romance that plays out on and off stage- but when an unexpected tragedy hits their new family, everything they know and love is tested. An intensely moving portrait of a relationship from beginning to end, propelled by a soundtrack of foot-stomping bluegrass, The Broken Circle Breakdown is a romantic drama of the highest order.